TINJAUAN KLIMATOLOGIS KEJADIAN HUJAN DI MUSIM KEMARAU PADA DASARIAN I SEPTEMBER 2020 DI SULAWESI TENGGARA - Qothrunada, Dewi Tamara; Risnayah, Siti (Jurnal Widya Climago, 2020)
In September, the Southeast Sulawesi region normally experiences a dry season. However, there are still rainevents with low to high intensity that occur in Southeast Sulawesi during the first decade of September 2020 (1-10 September). Rainfall that exceeds 100 millimeters in a decade in an area during the dry season indicates thatthere are significant weather disturbance factors that play a role in the formation of a large and extensiveconvective cloud system. Regional and local scale weather analyzes were conducted to identify weatherdisturbances that contributed to these events. Based on the results of monitoring rainfall observations,atmospheric dynamics data, and sea surface temperature, the rain event during the first decade of September2020 was an extreme event caused by disturbances in wind patterns around Kalimantan and Sulawesi, warmingsea surface temperatures in Indonesia and activate of weak La Nina, disturbance of easterly winds, and a fairly massive increase in air masses in the Southeast Sulawesi region. This rain event is also supported by the activeflow of cold wind (westerly wind) from mainland Asia in the upper layer.